Literacy Culture in Building Student Learning Independence - Yulianingsih, Wiwin; Masitoh, Siti; Mariono, Andi; Naqiyah, Najlatun; Kiettkunwong, Narong (Universitas Negeri Semarang, 2024)
The low quality of human resources (HR) is motivated by the low literacy skills of the community, including students as academics. Literacy is seen as the ability to manage information as well as utilize or implement it in everyday life, so learning independence is very necessary to be able to achieve learning success in the Society 5.0 era. The aim of this research is to analyze and describe literacy culture in creating learning independence for FIP UNESA students in the Era of Society 5.0. This type of research is survey research with descriptive quantitative research methods. Data collection techniques using online observation and questionnaires via Google Form. Then the analysis and applied techniques are through data examination, data classification, data tabulation, calculating data frequencies, further calculations, visualizing data, and interpreting data. The results of research on literacy culture in building the independence of FIP UNESA students in the Era of Society 5.0 stated that based on the results of the average answers from 208 respondents, 23 answers had a good classification and 5 questions had a very good classification. Meanwhile, the average results of the answers from 208 respondents were 17 answers had a good classification and 2 questions had a very good classification.